Multi-scale toughening shrinkage-compensating C80 high-crack-resistance self-compacting concrete and preparation method thereof
By using low-shrinkage crack-resistant composite cement, multi-scale hybrid fibers and nano-silica modified water-based polyurethane in C80 concrete, the compressive, flexural and crack-resistant problems of C80 concrete in large span bridges are solved. It achieves high strength, high toughness and low shrinkage characteristics, and is suitable for the construction of heavy-load, high piers and large-span bridges.
Patent Information
- Application Number
- CN202411425197.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing C80 concrete has low compressive strength, low flexural strength and low bending toughness in the construction of large span bridges, resulting in high construction difficulty and insufficient safety, and is prone to shrinkage and cracking, making it difficult to meet heavy loads, high piers, and large span bridges. demand.
Using multi-scale toughening compensation shrinkage C80 high-cracking self-solid concrete, it uses low-shrinkage crack-resistant composite cement, multi-scale mixed fibers, nano-silica modified water-based polyurethane emulsion, high-efficiency water-reducing and slump-retaining, stable bubble-stable and viscosm-adjusted and tack-adjusted The combination of agents forms concrete with high strength, low shrinkage, high toughness and crack resistance.
Improve the tensile strength and toughness of C80 concrete, reduce the risk of shrinkage and cracking, achieve good fluidity and long-term pumping stability under low water-adhesive ratio, is suitable for the construction of large span bridges, and improves the safety of the project. Sex and reliability.
Smart Images

Figure BDA0005081948970000191 
Figure FDA0005081948960000011 
Figure FDA0005081948960000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a multi-scale toughening and shrinkage compensating C80 high-crack resistance self-compacting concrete and a preparation method thereof. Background Art
[0002] There are many deep mountain valleys and turbulent rivers in western my country, and the planned highways and railways have a high ratio of bridges and tunnels, which requires heavy-duty, high-pier, and long-span bridges. Reinforced concrete rigid skeleton arch bridges have the characteristics of both steel tube concrete and steel-framed concrete, and have good rigidity and stability. They are competitive in the design of long-span bridge structures, but they also have disadvantages such as many structural system conversions, complex structural forces, and long construction periods, which are not suitable for the construction needs of bridges in specific complex mountainous areas.
[0003] Reinforced concrete box arches have low construction costs, large spans, and high bearing capacity. Compared with reinforced concrete rigid frames, reinforced concrete box arches have the advantages of not being restricted by geographical location, low equipment lifting requirements, and a shorter construction period. However, at present, reinforced concrete box arches are mostly cast with C50-C60 concrete, and the wall thickness of the box arch ranges from 50-120cm. The deadweight is heavy, so the span of the hanging basket is generally not more than 200m. How to increase the span of the hanging basket of reinforced concrete box arches and solve the problems of high construction difficulty and high risk is the current research focus.
[0004] The use of C80 concrete to design and prepare the box wall can not only improve the overall performance and service life of the structure, but also reduce the wall thickness and self-weight, increase the span of the reinforced concrete box arch hanging basket, ensure the safety and reliability of the project, and reduce maintenance and repair costs. However, the current C80 concrete has defects such as low compressive strength, low flexural strength, and low bending toughness. Based on this, it is necessary to improve the existing C80 concrete. Summary of the invention
[0005] In view of this, the present invention proposes a multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete and a preparation method thereof, so as to solve or partially solve the problems existing in the prior art.
[0006] In the first aspect, the present invention provides a multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete, comprising the following raw materials: low shrinkage and crack resistance composite cement 400-500 kg / m 3 , Viscosity-adjusting and reinforcing mineral admixtures 150~200kg / m 3 , Fine aggregate 680~800kg / m 3 , high strength coarse aggregate 950~1100kg / m 3 , Multi-scale mixed fiber 50~80kg / m 3, Nano-silicon dioxide modified waterborne polyurethane emulsion 9~20kg / m 3 , high efficiency water reduction, collapse protection, foam stabilization and viscosity adjustment admixture 9~11kg / m 3 , Water 140~160kg / m 3 ;
[0007] The low shrinkage and crack-resistant composite cement is compounded by P·II 52.5 silicate cement and P·II 42.5 high-iron phase sulphoaluminate cement containing Q phase.
[0008] Preferably, the P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is prepared by the following method:
[0009] Mix fly ash, limestone, magnesite and calcium sulfate to obtain a first mixed material;
[0010] The first mixed material is heated to 1290-1350° C. at 5-10° C. / min and calcined, and kept at this temperature for 40-45 minutes to obtain Q phase-calcium sulfoaluminate clinker;
[0011] Mixing red mud, limestone, bauxite and calcium sulfate to obtain a second mixture;
[0012] The second mixed material is heated to 1290-1350°C at a rate of 5-10°C / min and calcined, and kept at this temperature for 40-45 minutes to obtain Sulphoaluminate cement clinker;
[0013] Q phase-calcium sulphoaluminate clinker, The sulphoaluminate cement clinker was mixed to obtain the Q-rich P·II 42.5 high iron phase sulphoaluminate cement clinker;
[0014] The Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker is mixed with dihydrate gypsum and ground to a specific surface area of 330-350m 2 / kg, that is, P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is obtained.
[0015] Preferably, the multi-scale hybrid fibers are composed of high-strength fine straight steel fibers, multi-anchor steel fibers, temperature shrinkage-induced organic fibers, CaCO3 whiskers and CaSO4 whiskers;
[0016] The high-strength fine straight steel fiber has a nominal length of 6 to 13 mm, an equivalent diameter of 0.20 ± 0.02 mm, a breaking strength of ≥ 2200 MPa, an elastic modulus of 190 to 230 GPa, and a tensile strength of 400 to 2100 MPa;
[0017] The multi-anchor steel fiber has a nominal length of 6 to 13 mm, an equivalent diameter of 0.2 ± 0.02 mm, a breaking strength of ≥ 1200 MPa, an elastic modulus of 210 to 230 GPa, and a tensile strength of 550 to 2150 MPa;
[0018] The temperature shrinkage induced organic fiber has a tensile strength of 500-1200 MPa, an elastic modulus of 7-35 GPa, a shrinkage rate of 0.5%-12%, and a response temperature of 30°C-100°C;
[0019] The CaSO4 whisker has a nominal length of 100-300 μm, an equivalent diameter of 1-3 μm, and an apparent density of 2.3-2.6 g / cm 3 ;
[0020] The CaCO3 whisker has a nominal length of 10 to 20 μm and an elastic modulus of 410 to 710 GPa.
[0021] Preferably, the mass ratio of the P·II 52.5 silicate cement to the P·II 42.5 high iron phase sulphoaluminate cement containing the Q phase is (60-70):(30-40);
[0022] The mass ratio of the fly ash, limestone, magnesite and calcium sulfate is (60-70):(15-20):(5-10):(5-10);
[0023] The mass ratio of the red mud, limestone, bauxite and calcium sulfate is (40-45):(25-30):(20-25):(5-10);
[0024] The Q phase-calcium sulphoaluminate clinker, The mass ratio of sulphoaluminate cement clinker is (50-60):(40-50);
[0025] The mass of the dihydrate gypsum is 10-15% of the mass of the Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker;
[0026] The addition amount of the high-strength fine straight steel fiber is 20-30 kg / m 3 ;
[0027] The addition amount of the multi-anchor steel fiber is 20-30 kg / m 3 ;
[0028] The amount of the temperature shrinkage-induced organic fiber added is 1-2 kg / m 3 ;
[0029] The amount of CaCO3 whiskers added is 5-8 kg / m 3
[0030] The amount of CaSO4 whiskers added is 5-8 kg / m 3 .
[0031] Preferably, the viscosity-adjusting and reinforcing mineral admixture comprises a mixture of fly ash microbeads and silica fume;
[0032] The amount of fly ash microbeads added is 75-100 kg / m 3 ;
[0033] The amount of silica fume added is 75-100 kg / m 3 ;
[0034] The fly ash microbeads have a 28d activity index of 107% and a water requirement ratio of 101%;
[0035] The SiO2 mass content in the silica ash is ≥91%, and the specific surface area is ≥20100m 2 / kg, 28d activity index ≥101%.
[0036] Preferably, the preparation method of the nano-silicon dioxide modified waterborne polyurethane emulsion is:
[0037] Adding nano-silicon dioxide into an aqueous polyurethane emulsion, and uniformly dispersing the nano-silicon dioxide in the aqueous polyurethane emulsion by ultrasonic dispersion or high shear stirring, thereby obtaining a nano-silicon dioxide-modified aqueous polyurethane emulsion;
[0038] The nano silicon dioxide has a particle size of 10 to 20 nm and a specific surface area of 200 to 400 m 2 / g, apparent density is 2.2~2.5g / cm 3 .
[0039] Preferably, the highly efficient water-reducing, slump-retaining, foam-stabilizing and viscosity-adjusting admixture comprises a polycarboxylate water-reducing agent mother liquor, an air-entraining agent, boric acid, a tetramethyldecynediol foam control agent, a polyhydroxycarboxylate retarder and water;
[0040] Among them, the amount of polycarboxylate water-reducing agent mother liquor added is 6.1-6.2 kg / m 3 ;
[0041] The amount of air entraining agent added is 0.003~0.005kg / m 3 ;
[0042] The amount of boric acid added is 0.11~0.13kg / m 3 ;
[0043] The amount of tetramethyldecynediol foam control agent added is 0.01-0.02 kg / m 3 ;
[0044] The amount of polyhydroxycarboxylate retarders added is 0.11-0.13 kg / m 3 ;
[0045] The amount of water added is 3.5~3.7kg / m 3 .
[0046] Preferably, the fine aggregate is river sand, and the apparent density of the fine aggregate is 2560-2650 kg / m 3 , the fineness modulus is 2.8.
[0047] Preferably, the high-strength coarse aggregate is a basalt coarse aggregate with a continuous gradation of 5 to 16 mm, wherein the basalt coarse aggregate has a strength of 169 MPa, a crushing value of 10%, a needle-like content of ≤5%, and an apparent density of 2900 to 3000 kg / m 3 .
[0048] In a second aspect, the present invention further provides a method for preparing the multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete, comprising the following steps:
[0049] Low shrinkage and crack-resistant composite cement, viscosity-adjusting and reinforcing mineral admixtures, fine aggregate, high-strength coarse aggregate and multi-scale mixed fibers are mixed and stirred, and then water, high-efficiency water-reducing and collapse-preserving, foam-stabilizing and viscosity-adjusting admixtures, and nano-silicon dioxide-modified water-based polyurethane emulsion are added and stirred to obtain multi-scale toughening and shrinkage-compensating C80 high crack-resistant self-compacting concrete.
[0050] The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete and its preparation method have the following beneficial effects compared with the prior art:
[0051] 1. The present invention adopts low shrinkage and crack-resistant composite cement to compensate the shrinkage of C80 concrete, avoiding the disadvantage that the general expansion agent is difficult to play a role due to the low water-cement ratio design of ordinary C80 concrete, and solving the problem of easy shrinkage and cracking of C80 concrete. The present invention adopts multi-scale hybrid fiber toughening and crack resistance, and uses high-strength fine steel fiber, multi-anchor steel fiber, and temperature shrinkage induced organic fiber to improve the toughness of C80 concrete and the crack resistance in the temperature rise / fall stage on a macro scale; CaCO3 and CaSO4 composite whiskers and nano-silicon dioxide modified waterborne polyurethane are used to form a uniform three-dimensional toughening network inside the cementitious slurry, and the tensile strength and toughness of C80 concrete are improved on a micron scale. Make C80 concrete have the characteristics of low shrinkage, high toughness, and high crack resistance.
[0052] 2. The present invention adopts viscosity-adjusting and reinforcing mineral admixtures and high-efficiency water-reducing, slump-preserving, foam-stabilizing and viscosity-adjusting admixtures to improve the fluidity of concrete; by adding polycarboxylic acid water-reducing agent mother liquor and fly ash microspheres, the fluidity and workability of concrete are improved; by adding high-efficiency air-entraining agent and tetramethyldecynediol foam control agent, a large number of fine bubbles of 50 to 100 microns are introduced, so as to achieve good fluidity, cohesiveness and long-term pumping stability of C80 concrete under low water-binder ratio, thereby realizing the self-compacting design of C80 concrete. DETAILED DESCRIPTION
[0053] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0055] The embodiment of the present application provides a multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete, including the following raw materials: low shrinkage and crack resistance composite cement 400-500 kg / m 3 , Viscosity-adjusting and reinforcing mineral admixtures 150~200kg / m 3 , Fine aggregate 680~800kg / m 3 , high strength coarse aggregate 950~1100kg / m 3 , Multi-scale mixed fiber 50~80kg / m 3 , Nano-silicon dioxide modified waterborne polyurethane emulsion 9~20kg / m 3 , high efficiency water reduction, collapse protection, foam stabilization and viscosity adjustment admixture 9~11kg / m 3 , Water 140~160kg / m 3 ;
[0056] The low shrinkage and crack-resistant composite cement is compounded by P·II 52.5 silicate cement and P·II 42.5 high-iron phase sulphoaluminate cement containing Q phase.
[0057] The present invention aims to develop an organic and inorganic composite multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete by rationally utilizing P·II 42.5 high iron phase sulphoaluminate cement containing Q phase, nano-silicon dioxide modified waterborne polyurethane, multi-scale hybrid fibers and high-efficiency water-reducing, slump-retaining, foam-stabilizing and viscosity-adjusting admixtures, so as to adapt to the construction of heavy-load, high-pier and long-span bridges. The P·II high iron phase sulphoaluminate cement containing Q phase is composed of minerals fired at 1290-1350°C, with 25%-30% Q phase minerals (Ca 20 Al 26 Mg3Si3O 68 ), The clinker of mineral, 20%-25% C4AF mineral, 0%-5% C2S mineral and 10%-15% dihydrate gypsum are ground together to a specific surface area of 330-350m 2 / kg. The low shrinkage and crack-resistant composite cement has a 3d compressive strength of 28.5MPa, a 28d compressive strength of 57.8MPa, a 3d flexural strength of 6.8MPa, and a 28d flexural strength of 8.9MPa.
[0058] In some embodiments, the P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is prepared by the following method:
[0059] Mix fly ash, limestone, magnesite and calcium sulfate to obtain a first mixed material;
[0060] The first mixed material is heated to 1290-1350° C. at 5-10° C. / min and calcined, and kept at this temperature for 40-45 minutes to obtain Q phase-calcium sulfoaluminate clinker;
[0061] Mixing red mud, limestone, bauxite and calcium sulfate to obtain a second mixture;
[0062] The second mixed material is heated to 1290-1350°C at a rate of 5-10°C / min and calcined, and kept at this temperature for 40-45 minutes to obtain Sulphoaluminate cement clinker;
[0063] Q phase-calcium sulphoaluminate clinker, The sulphoaluminate cement clinker was mixed to obtain the Q-rich P·II 42.5 high iron phase sulphoaluminate cement clinker;
[0064] The Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker is mixed with dihydrate gypsum and ground to a specific surface area of 330-350m2 / kg, that is, P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is obtained.
[0065] The Q phase and C4AF mineral phase in the P·II 42.5 high-iron phase sulphoaluminate cement used in the present invention can coordinately regulate the microstructure of the C-(A)-SH gel of the composite cement hydration product to form a high-Al-doped C-(A)-SH gel, thereby improving the mechanical properties and toughness of the C-(A)-SH gel; at the same time, C4AF reacts with gypsum to generate needle-rod-shaped calcium sulfonate crystals that are uniformly distributed in the C-(A)-SH gel to form calcium sulfonate microcrystals to toughen the C-(A)-SH gel, thereby significantly improving the strength and toughness of the composite cement hydrated gelled slurry; in addition, the Q phase in the high-iron phase sulphoaluminate cement is hydrated to form magnesium hydroxide and The mineral phase is hydrated to form calcium sulfide, and the expansive hydration products such as magnesium hydroxide and calcium sulfide compensate for the shrinkage of C80 concrete, which can improve the concrete's anti-cracking performance.
[0066] In some embodiments, the multi-scale hybrid fibers are composed of high-strength fine straight steel fibers, multi-anchor steel fibers, temperature shrinkage-induced organic fibers, CaCO3 whiskers, and CaSO4 whiskers;
[0067] The nominal length of high-strength fine straight steel fiber is 6-13mm, the equivalent diameter is 0.20±0.02mm, the breaking strength is ≥2200MPa, the elastic modulus is 190-230GPa, and the tensile strength is 400-2100MPa;
[0068] The nominal length of the multi-anchor steel fiber is 6-13mm, the equivalent diameter is 0.2±0.02mm, the breaking strength is ≥1200MPa, the elastic modulus is 210-230GPa, and the tensile strength is 550-2150Mpa;
[0069] The tensile strength of the temperature shrinkage-induced organic fiber is 500-1200 MPa, the elastic modulus is 7-35 GPa, the shrinkage rate is 0.5%-12%, and the response temperature is 30°C-100°C;
[0070] The nominal length of CaSO4 whiskers is 100-300 μm, the equivalent diameter is 1-3 μm, and the apparent density is 2.3-2.6 g / cm 3 ;
[0071] The nominal length of CaCO3 whiskers is 10-20 μm, and the elastic modulus is 410-710 GPa.
[0072] The present invention adopts multi-scale hybrid fiber toughening and crack resistance. By adding high-strength fine steel fibers and multi-anchor steel fibers into C80 concrete, stress is dispersed, micro cracks are bridged, and the toughness of C80 concrete is improved on a macro scale. By adding temperature shrinkage-induced fibers, the pre-compression stress generated on the cementitious slurry during the hydration and heat release of the cementitious slurry by the reconstruction of fiber molecules and the shrinkage, the temperature difference stress inside and outside the concrete is partially or completely offset, thereby improving the crack resistance of the concrete in the temperature rise / fall stage. By adding CaCO3 and CaSO4 composite whiskers, more nucleation sites and additional SO4 are provided for the formation of ettringite. 2- , filling micro cracks and micro pores, improving the compactness and durability of concrete. By adding nano-silicon dioxide modified waterborne polyurethane, a uniform three-dimensional toughening network is formed inside the cement paste, which enhances the bonding force inside the concrete, improves the stability of the overall structure, and improves the tensile strength and toughness of C80 concrete at the micro-nano scale.
[0073] In some embodiments, the mass ratio of P·II 52.5 silicate cement to P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is (60-70):(30-40).
[0074] In some embodiments, the mass ratio of fly ash, limestone, magnesite and calcium sulfate is (60-70):(15-20):(5-10):(5-10).
[0075] In some embodiments, the mass ratio of red mud, limestone, bauxite and calcium sulfate is (40-45):(25-30):(20-25):(5-10).
[0076] In some embodiments, Q phase - calcium sulfoaluminate clinker, The mass ratio of sulphoaluminate cement clinker is (50-60):(40-50).
[0077] In some embodiments, the mass of the dihydrate gypsum is 10-15% of the mass of the Q-phase P·II 42.5 high-iron phase sulphoaluminate cement clinker.
[0078] In some embodiments, the amount of high-strength fine straight steel fiber added is 20-30 kg / m 3 .
[0079] In some embodiments, the amount of multi-anchor steel fiber added is 20-30 kg / m 3 .
[0080] In some embodiments, the amount of the temperature shrinkage-inducing organic fiber added is 1-2 kg / m 3 .
[0081] In some embodiments, the amount of CaCO3 whiskers added is 5-8 kg / m3 .
[0082] In some embodiments, the amount of CaSO4 whiskers added is 5-8 kg / m 3 .
[0083] In some embodiments, the viscosity-adjusting and reinforcing mineral admixture includes a mixture of fly ash microspheres and silica fume.
[0084] In some embodiments, the amount of fly ash microbeads added is 75-100 kg / m 3 .
[0085] In some embodiments, the amount of silica fume added is 75-100 kg / m 3 .
[0086] In some embodiments, the fly ash microspheres have a 28d activity index of 107% and a water demand ratio of 101%.
[0087] In some embodiments, the mass content of SiO2 in the silica ash is ≥ 91%, and the specific surface area is ≥ 20100m 2 / kg, 28d activity index ≥101%.
[0088] In some embodiments, the preparation method of nano-silicon dioxide modified waterborne polyurethane emulsion is:
[0089] Adding nano-silicon dioxide into an aqueous polyurethane emulsion, and uniformly dispersing the nano-silicon dioxide in the aqueous polyurethane emulsion by ultrasonic dispersion or high shear stirring, thereby obtaining a nano-silicon dioxide-modified aqueous polyurethane emulsion;
[0090] The particle size of nano-silicon dioxide is 10-20nm, and the specific surface area is 200-400m 2 / g, apparent density is 2.2~2.5g / cm 3 .
[0091] In some embodiments, the high-efficiency water-reducing, slump-preserving, foam-stabilizing and viscosity-adjusting admixture includes a polycarboxylate water-reducing agent mother solution, an air-entraining agent, boric acid, a tetramethyldecynediol foam control agent, a polyhydroxycarboxylate retarder and water.
[0092] Specifically, the mother liquor of polycarboxylate water-reducing agent has a water reduction rate of 30%-35% and a slump retention time of 2h-4h; the air-entraining agent introduces tiny bubbles, and the air content loss after standing for 1h is less than 1%; boric acid prolongs the initial setting time of concrete from 3h to 4h; the polyhydroxycarboxylate retarders prolong the initial setting time of concrete to 1h-4h.
[0093] In some embodiments, the amount of polycarboxylate water-reducing agent mother solution added is 6.1-6.2 kg / m 3 ;
[0094] The amount of air entraining agent added is 0.003~0.005kg / m 3 ;
[0095] The amount of boric acid added is 0.11~0.13kg / m 3 ;
[0096] The amount of tetramethyldecynediol foam control agent added is 0.01-0.02 kg / m 3 ;
[0097] The amount of polyhydroxycarboxylate retarders added is 0.11-0.13 kg / m 3 ;
[0098] The amount of water added is 3.5~3.7kg / m 3 .
[0099] The present invention adopts viscosity-adjusting and reinforcing mineral admixtures and high-efficiency water-reducing, slump-preserving and foam-stabilizing viscosity-adjusting admixtures to improve the fluidity of concrete; by adding polycarboxylic acid water-reducing agent mother liquor and fly ash microbeads, the fluidity and workability of concrete are improved; by adding high-efficiency air-entraining agent and tetramethyldecynediol foam control agent, a large number of fine bubbles of 50 to 100 microns are introduced, so that good fluidity, cohesiveness and long-term pumping stability of C80 concrete under low water-binder ratio are achieved, thereby realizing the self-compacting design of C80 concrete.
[0100] In some embodiments, the fine aggregate is river sand, and the apparent density of the fine aggregate is 2560-2650 kg / m 3 , the fineness modulus is 2.8.
[0101] In some embodiments, the high-strength coarse aggregate is a basalt coarse aggregate with a continuous gradation of 5 to 16 mm, wherein the basalt coarse aggregate has a strength of 169 MPa, a crushing value of 10%, a needle-like content of ≤5%, and an apparent density of 2900 to 3000 kg / m 3 .
[0102] In some embodiments, a method for preparing temperature shrinkage-induced organic fibers comprises the following steps:
[0103] S1. Two extruders are used to extrude the heat shrinkable core material mixture and the heat shrinkable skin material mixture into a die head with two cavities, wherein the heat shrinkable skin material enters the cavity corresponding to the skin material, and the heat shrinkable core material enters the cavity corresponding to the core material. The materials in the two cavities converge at the position of the spinneret of the extruder; wherein the spinneret has an inner ring and an outer ring, the inner ring of the spinneret is connected to the cavity of the core material, and the outer ring of the spinneret is connected to the cavity of the skin material, and the two molten materials are extruded (melt extrusion) through the spinneret, and stick together in the air, cooled by a cold water tank, and then drawn in hot water at 90-100°C to form a composite fiber with a skin-core structure;
[0104] S2, adding 1%-5% (mass concentration) silane coupling agent solution to the composite fiber obtained in step S1 for modification for 10-20 minutes, and then drying and indenting the surface to enhance its bonding performance with concrete slurry;
[0105] S3, adding the composite fiber obtained in step S2 into a modified polyvinyl alcohol solution to which an expansion component is added for coating and modification, taking out and drying, thereby obtaining a temperature shrinkage-induced organic fiber;
[0106] Among them, the heat shrinkable leather material mixture, each raw material and its mass percentage are: polyvinyl alcohol 97%, maleic anhydride grafted compatibilizer 1.5%, phthalate plasticizer 1.5%; the extrusion pressure of the leather material cavity is 8MPa, and the melting temperature is maintained at 250℃;
[0107] The heat shrinkable core material mixture, each raw material and its mass percentage are: polypropylene 98%, rigid nucleating agent 2% (aluminum aromatic carboxylate aluminum and sodium benzoate in a mass ratio of 1:1); the melting temperature of the heat shrinkable core material mixture is 200-280°C; the extrusion pressure of the corresponding cavity is 7-10MPa;
[0108] In the last extrusion section corresponding to the spinneret, the extrusion temperature of the two molten materials is maintained at a temperature suitable for both materials, that is, 200-220° C., and the extrusion pressure is 3-10 MPa.
[0109] In some embodiments, the coating modification temperature is room temperature and the time is 10 to 24 hours.
[0110] In some embodiments, the expansion agent is a compound of a calcium oxide expansion agent and a calcium sulfoaluminate expansion agent; preferably, the expansion agent is a compound of a calcium oxide expansion agent and a calcium sulfoaluminate expansion agent in a mass ratio of 1:40 to 50;
[0111] In some embodiments, the modified polyvinyl alcohol solution with added swelling component is obtained by uniformly mixing a polyvinyl alcohol solution (6 wt %) and a liquid swelling agent in a mass ratio of 7:3.
[0112] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete, comprising the following steps:
[0113] Low shrinkage and crack-resistant composite cement, viscosity-adjusting and reinforcing mineral admixtures, fine aggregate, high-strength coarse aggregate and multi-scale mixed fibers are mixed and stirred, and then water, high-efficiency water-reducing and collapse-preserving, foam-stabilizing and viscosity-adjusting admixtures, and nano-silicon dioxide-modified water-based polyurethane emulsion are added and stirred to obtain multi-scale toughening and shrinkage-compensating C80 high crack-resistant self-compacting concrete.
[0114] In some embodiments, low shrinkage and crack-resistant composite cement, viscosity-adjusting and reinforcing mineral admixtures, fine aggregate, high-strength coarse aggregate and multi-scale mixed fibers are mixed and stirred for 60 to 120 seconds, and then water, high-efficiency water-reducing and collapse-preserving, foam-stabilizing and viscosity-adjusting admixtures, and nano-silicon dioxide-modified water-based polyurethane emulsion are added and stirred for 120 seconds to obtain multi-scale toughening and shrinkage-compensating C80 high crack-resistant self-compacting concrete.
[0115] The present invention adopts P II 42.5 high iron phase sulphoaluminate cement containing Q phase (25%-30% Q phase mineral, 40%-45% Minerals, 20%-25% C4AF minerals, 5%-10% dihydrate gypsum) are compounded with PII 52.5 silicate cement to form a low shrinkage and crack-resistant composite cement; the Q phase, The C4AF mineral phase regulates the microstructure of C-(A)-SH gel to form calcium sulfonate microcrystal-toughened C-(A)-SH gel to compensate for shrinkage and enhance toughness; multi-scale hybrid fibers are used to enhance toughness and crack resistance. By adding high-strength fine steel fibers and multi-anchor steel fibers, stress is dispersed, microcracks are bridged, and the toughness of C80 concrete is improved on a macro scale; by adding temperature shrinkage-induced fibers, the temperature rise shrinkage characteristics are used to partially or completely offset the temperature difference stress inside and outside the concrete, thereby improving the crack resistance of concrete on a micro-meso scale; by adding CaCO3 and CaSO4 composite whiskers and nano-silica modified waterborne polyurethane, a uniform three-dimensional toughening network is formed inside the cementitious slurry, thereby improving the tensile strength and toughness of C80 concrete on a micron scale. By adding viscosity-adjusting and reinforcing mineral admixtures and highly efficient water-reducing, slump-retaining, foam-stabilizing and viscosity-adjusting admixtures, fly ash microspheres, polycarboxylic acid highly efficient water-reducing agent and air-entraining agent are used to reduce the viscosity of concrete and improve the fluidity of concrete; silica fume is used to improve the encapsulation of fibers and aggregates to prevent the sinking of fibers and aggregates during vibration; by adding highly efficient air-entraining agent and tetramethyldecynediol foam control agent, a large number of fine 50-100 micron bubbles are introduced to achieve good fluidity, cohesiveness and long-term pumping stability of C80 concrete under low water-cement ratio, thereby realizing the self-compacting design of C80 concrete. The organic and inorganic composite multi-scale toughening and shrinkage-compensating C80 highly crack-resistant self-compacting concrete of the present invention has the characteristics of high strength, high toughness, self-compacting and high crack resistance, which solves the problem of insufficient tensile strength of concrete and easy shrinkage cracking during the construction of large-span concrete box arch bridge hanging basket, and has important practical application value.
[0116] The present invention adopts low shrinkage and crack-resistant composite cement to compensate the shrinkage of C80 concrete, avoiding the drawback that the general expansion agent is difficult to play a role due to the low water-cement ratio design of ordinary C80 concrete, and solving the problem that C80 concrete is easy to shrink and crack. The present invention adopts multi-scale hybrid fiber toughening and crack resistance, and uses high-strength fine steel fiber, multi-anchor steel fiber, and temperature shrinkage induced organic fiber to improve the toughness of C80 concrete and the crack resistance in the temperature rise / fall stage on a macro scale; CaCO3 and CaSO4 composite whiskers and nano-silicon dioxide modified waterborne polyurethane are used to form a uniform three-dimensional toughening network inside the cementitious slurry, and the tensile strength and toughness of C80 concrete are improved on a micron scale. Make C80 concrete have the characteristics of low shrinkage, high toughness, and high crack resistance.
[0117] The following further describes the multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete and its preparation method of the present invention with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0118] The method for preparing the temperature shrinkage-induced organic fiber in the following embodiment comprises the following steps:
[0119] S1. Two extruders are used to extrude the heat shrinkable core material mixture and the heat shrinkable skin material mixture into a die head with two cavities, wherein the heat shrinkable skin material enters the cavity corresponding to the skin material, and the heat shrinkable core material enters the cavity corresponding to the core material. The materials in the two cavities converge at the position of the spinneret of the extruder; wherein the spinneret has an inner ring and an outer ring, the inner ring of the spinneret is connected to the cavity of the core material, and the outer ring of the spinneret is connected to the cavity of the skin material, and the two molten materials are extruded (melt extrusion) through the spinneret, and stick together in the air, cooled by a cold water tank, and then drawn in 95°C hot water to form a composite fiber with a skin-core structure;
[0120] S2, adding 3% (mass concentration) silane coupling agent (specifically octamethylcyclotetrasiloxane) solution to the composite fiber obtained in step S1 for modification for 20 minutes, and then drying and indenting the surface to enhance its bonding performance with the concrete slurry;
[0121] S3, adding the composite fiber obtained in step S2 to a modified polyvinyl alcohol solution with an expansion component added thereto, and performing coating modification at room temperature for 20 hours, taking out and drying, thereby obtaining a temperature shrinkage induced organic fiber; the modified polyvinyl alcohol solution with an expansion component added thereto is obtained by uniformly mixing a polyvinyl alcohol solution (6wt%) and an expansion agent at a mass ratio of 7:3, and the expansion agent is composited by a calcium oxide expansion agent and a calcium sulfoaluminate expansion agent at a mass ratio of 1:45;
[0122] Among them, the heat shrinkable leather material mixture, each raw material and its mass percentage are: polyvinyl alcohol 97%, maleic anhydride grafted compatibilizer (model provided by Dongguan Shenghao Plastic Raw Materials Co., Ltd., model PP-G-MAH) 1.5%, phthalate plasticizer 1.5%; the extrusion pressure of the leather material cavity is 8MPa, and the melting temperature is maintained at 250°C;
[0123] The heat shrinkable core material mixture, each raw material and its mass percentage are: polypropylene 98%, rigid nucleating agent 2% (aluminum aromatic carboxylate aluminum and sodium benzoate in a mass ratio of 1:1); the melting temperature of the heat shrinkable core material mixture is 210°C; the extrusion pressure of the corresponding cavity is 8MPa;
[0124] In the last extrusion section corresponding to the spinneret, the extrusion temperature of the two molten materials is maintained at a temperature suitable for both materials, i.e., 215°C, and the extrusion pressure is 6MPa;
[0125] The average diameter of the obtained core fiber is 0.15 mm, and the thickness of the skin fiber is 0.08 mm;
[0126] The obtained temperature shrinkage induced organic fiber has a length of 10 mm to 12 mm, a shrinkage rate of 0.5% to 12%, a response temperature of 30° C. to 100° C., a tensile strength of 700 MPa, and an elastic modulus of 15.0 GPa.
[0127] Example 1
[0128] This embodiment provides a multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete, including the following raw materials: low shrinkage and crack resistance composite cement 450kg / m 3 , Viscosity-adjusting and reinforcing mineral admixture 150kg / m 3 , fine aggregate 708kg / m 3 , high strength coarse aggregate 1025kg / m 3 , multi-scale hybrid fiber 57kg / m 3 , Nano-silicon dioxide modified waterborne polyurethane emulsion 12kg / m 3 , high efficiency water reduction, collapse protection, foam stabilization and viscosity adjustment admixture 9.9kg / m 3 , water 144kg / m 3 ;
[0129] The low shrinkage and crack-resistant composite cement is compounded by P·II 52.5 silicate cement and P·II 42.5 high-iron phase sulphoaluminate cement containing Q phase; the mass ratio of P·II 52.5 silicate cement to P·II 42.5 high-iron phase sulphoaluminate cement containing Q phase is 60:40;
[0130] P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is prepared by the following method:
[0131] S1, mixing fly ash, limestone, magnesite and calcium sulfate to obtain a first mixture; the mass ratio of fly ash, limestone, magnesite and calcium sulfate is 60:20:5:10;
[0132] S2, heating the first mixed material to 1330° C. at a rate of 5° C. / min and calcining the mixture, and keeping the temperature for 40 min to obtain Q phase-calcium sulfoaluminate clinker;
[0133] S2, mixing red mud, limestone, bauxite and calcium sulfate to obtain a second mixture; the mass ratio of red mud, limestone, bauxite and calcium sulfate is 45:25:25:5;
[0134] S3, the second mixed material is heated to 1300°C at 5°C / min and calcined, and kept at this temperature for 45 minutes to obtain Sulphoaluminate cement clinker;
[0135] S4, Q phase - calcium sulphoaluminate clinker, The sulphoaluminate cement clinker is mixed in a mass ratio of 50:50 to obtain a Q-rich P·II 42.5 high iron phase sulphoaluminate cement clinker;
[0136] S5, after mixing the Q-rich P·II 42.5 high iron phase sulphoaluminate cement clinker with dihydrate gypsum, grind it to a specific surface area of 340m 2 / kg, that is, P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is obtained; the mass of dihydrate gypsum is 10% of the mass of Q phase-rich P·II 42.5 high iron phase sulphoaluminate cement clinker;
[0137] Viscosity-adjusting and reinforcing mineral admixtures including fly ash microspheres 75kg / m 3 、Silica fume 75kg / m 3 The fly ash microspheres have an activity index of 107% at 28 days and a water requirement of 101%. The SiO2 mass content in the silica ash is ≥91% and the specific surface area is ≥20100m 2 / kg, 28d activity index ≥101%;
[0138] The fine aggregate is river sand, and the apparent density of fine aggregate is 2600kg / m 3 , fineness modulus is 2.8;
[0139] High-strength coarse aggregate is basalt coarse aggregate with continuous grading of 5-16 mm. The strength of basalt coarse aggregate is 169 MPa, the crushing value is 10%, the needle-like content is ≤5%, and the apparent density is 3000 kg / m 3 ;
[0140] The preparation method of nano-silicon dioxide modified waterborne polyurethane emulsion is as follows:
[0141] Nano-silicon dioxide is added to the aqueous polyurethane emulsion, and the nano-silicon dioxide is evenly dispersed in the aqueous polyurethane emulsion by ultrasonic dispersion to obtain the nano-silicon dioxide modified aqueous polyurethane emulsion; the particle size of the nano-silicon dioxide is 15nm, and the specific surface area is 300m 2 / g, apparent density is 2.3g / cm 3 ;
[0142] The multi-scale hybrid fibers are composed of high-strength fine straight steel fibers, multi-anchor steel fibers, temperature shrinkage-induced organic fibers, CaCO3 whiskers and CaSO4 whiskers;
[0143] The high-strength fine straight steel fiber is produced by Wuhan Xintu Engineering New Materials Technology Co., Ltd., with a nominal length of 13mm, an equivalent diameter of 0.20±0.02mm, a breaking strength of ≥2200MPa, an elastic modulus of 210GPa, and a tensile strength of 1300Mpa;
[0144] The multi-anchor steel fiber is produced by Wuhan Xintu Engineering New Materials Co., Ltd., with a nominal length of 13 mm, an equivalent diameter of 0.2 ± 0.02 mm, a breaking strength ≥ 1200 MPa, an elastic modulus of 220 GPa, and a tensile strength of 1400 MPa;
[0145] The CaSO4 whiskers were produced by Lingshou County Chuangbo Products Co., Ltd. in Hebei Province. The nominal length was 200 μm, the equivalent diameter was 2 μm, and the apparent density was 2.4 g / cm 3 ;
[0146] The CaCO3 whiskers were produced by Chuangbo Products Co., Ltd., Lingshou County, Hebei Province, with a nominal length of 15 μm and an elastic modulus of 610 GPa;
[0147] The water-based polyurethane emulsion was produced by Anhui Dawei Huatai New Material Technology Co., Ltd., model AH-1704, with a solid content of 30%;
[0148] The addition amount of high-strength fine straight steel fiber is 20kg / m 3 ;
[0149] The amount of multi-anchor steel fiber added is 25kg / m 3 ;
[0150] The addition amount of temperature shrinkage induced organic fiber is 2kg / m 3 ;
[0151] The amount of CaCO3 whiskers added is 5kg / m 3 ;
[0152] The amount of CaSO4 whiskers added is 5kg / m 3 ;
[0153] The high-efficiency water-reducing, slump-retaining, foam-stabilizing and viscosity-adjusting admixture includes polycarboxylate water-reducing agent mother liquor, air-entraining agent, boric acid, tetramethyldecynediol foam control agent, polyhydroxycarboxylate retarder and water; the addition amount of polycarboxylate water-reducing agent mother liquor is 6.138kg / m 3 ; The amount of air entraining agent added is 0.004kg / m 3 ; Boric acid addition amount is 0.12kg / m 3 ; Tetramethyldecynediol foam control agent added in an amount of 0.01kg / m 3 ; The amount of polyhydroxycarboxylate retarder added is 0.12kg / m 3 ; Water addition amount is 3.508kg / m 3 ;
[0154] Among them, the mother solution of polycarboxylate water reducer (water reduction rate is 30%-35%, collapse time is 2h-4h) is -HS polycarboxylic acid slow-release water-reducing agent mother liquor, produced by Jiangsu Subote New Materials Co., Ltd.; air-entraining agent is -III type high-efficiency air entraining agent, produced by Jiangsu Subot New Materials Co., Ltd.; boric acid is a white crystalline powder, produced by Tianjin Beichen District Fangzheng Reagent Factory; tetramethyldecynediol foam control agent, produced by Jiangsu Subot New Materials Co., Ltd.; polyhydroxycarboxylate retarders are -SR(II) powder retarder, produced by Jiangsu Subote New Materials Co., Ltd.;
[0155] The preparation method of the multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete comprises the following steps:
[0156] Low shrinkage and crack-resistant composite cement, viscosity-adjusting and reinforcing mineral admixtures, fine aggregate, high-strength coarse aggregate and multi-scale mixed fibers are mixed and stirred for 100 seconds, and then water, high-efficiency water-reducing and collapse-preserving, foam-stabilizing and viscosity-adjusting admixtures, and nano-silica-modified water-based polyurethane emulsion are added and stirred for 120 seconds to obtain multi-scale toughening and shrinkage-compensating C80 high crack-resistant self-compacting concrete.
[0157] Comparative Example 1
[0158] The C80 concrete provided in this comparative example is the same as that in Example 1, except that water-based polyurethane emulsion is used instead of nano-silicon dioxide-modified water-based polyurethane emulsion, and the rest is the same as that in Example 1.
[0159] Comparative Example 2
[0160] The C80 concrete provided in this comparative example is the same as that in Example 1, except that it does not contain the nano-silicon dioxide modified waterborne polyurethane emulsion, and the rest is the same as that in Example 1.
[0161] Comparative Example 3
[0162] The C80 concrete provided in this comparative example is the same as that in Example 1, except that a common polycarboxylate water-reducing agent is used instead of a high-efficiency water-reducing, slump-retaining, foam-stabilizing, and viscosity-adjusting admixture. The rest is the same as that in Example 1.
[0163] Comparative Example 4
[0164] The C80 concrete provided in this comparative example is the same as that in Example 1, except that it does not contain CaCO3 whiskers and CaSO4 whiskers, and the rest is the same as that in Example 1.
[0165] Comparative Example 5
[0166] The C80 concrete provided in this comparative example is the same as that in Example 1, except that P·II 52.5 silicate cement is used instead of low shrinkage and crack-resistant composite cement, and the rest is the same as that in Example 1.
[0167] Performance Testing
[0168] The properties of C80 concrete in Example 1 and Comparative Examples 1 to 5 were tested, and the results are shown in Table 1 below.
[0169] Table 1 - Performance of C80 concrete in different examples and comparative examples
[0170]
[0171] The above results show that the organic and inorganic composite multi-scale toughening and shrinkage-reducing C80 high crack resistance self-compacting concrete obtained by the present invention has good working performance, mechanical properties and volume stability, and the compressive strength of the concrete is ≥90MPa. In addition, by comparing Example 1 and Comparative Examples 1 to 2, it can be seen that the water-based polyurethane emulsion has a significant improvement effect on the flexural strength and bending toughness of concrete, and the effect is better after adding nano-silicon dioxide modified water-based polyurethane. By comparing Example 1 and Comparative Example 3, it is found that high-efficiency water-reducing and slump-preserving, foam-stabilizing and viscosity-adjusting admixtures can improve the workability of C80 concrete. Using ordinary polycarboxylic acid water-reducing agent, the expansion of C80 concrete is only 590mm. By comparing Example 1 and Comparative Example 4, it is found that CaCO3 and CaSO4 composite whiskers can improve the bending toughness of C80 concrete, but reduce the fluidity of concrete. By comparing Example 1 and Comparative Example 5, it is found that the low shrinkage and crack-resistant composite cement can compensate for the shrinkage of C80 concrete and reduce the 56d volume shrinkage rate; and the low shrinkage and crack-resistant composite cement can increase the flexural toughness index of C80 concrete to 10.7.
[0172] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0173] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.
Claims
1. A multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete, characterized in that: Includes the following raw materials: low shrinkage and crack-resistant composite cement 400-500kg / m 3 , Viscosity-adjusting and reinforcing mineral admixtures 150~200kg / m 3 , Fine aggregate 680~800kg / m 3 , high strength coarse aggregate 950~1100kg / m 3 , Multi-scale mixed fiber 50~80kg / m 3 , Nano-silicon dioxide modified waterborne polyurethane emulsion 9~20kg / m 3 , high efficiency water reduction, collapse protection, foam stabilization and viscosity adjustment admixture 9~11kg / m 3 , Water 140~160kg / m 3 ; The low shrinkage and crack-resistant composite cement is compounded by P·II 52.5 silicate cement and P·II 42.5 high-iron phase sulphoaluminate cement containing Q phase.
2. The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to claim 1, characterized in that: The P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is prepared by the following method: Mix fly ash, limestone, magnesite and calcium sulfate to obtain a first mixed material; The first mixed material is heated to 1290-1350° C. at 5-10° C. / min and calcined, and kept at this temperature for 40-45 minutes to obtain Q phase-calcium sulfoaluminate clinker; Mixing red mud, limestone, bauxite and calcium sulfate to obtain a second mixture; The second mixed material is heated to 1290-1350°C at a rate of 5-10°C / min and calcined, and kept at this temperature for 40-45 minutes to obtain Sulphoaluminate cement clinker; Q phase-calcium sulphoaluminate clinker, The sulphoaluminate cement clinker is mixed to obtain the Q-rich P·II42.5 high iron phase sulphoaluminate cement clinker; The Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker is mixed with dihydrate gypsum and ground to a specific surface area of 330-350m 2 / kg, that is, P·II 42.5 high iron phase sulphoaluminate cement containing Q phase is obtained.
3. The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to claim 2, characterized in that: The multi-scale hybrid fiber is composed of high-strength fine straight steel fiber, multi-anchor steel fiber, temperature shrinkage induced organic fiber, CaCO3 whisker and CaSO4 whisker; The high-strength fine straight steel fiber has a nominal length of 6 to 13 mm, an equivalent diameter of 0.20 ± 0.02 mm, a breaking strength of ≥ 2200 MPa, an elastic modulus of 190 to 230 GPa, and a tensile strength of 400 to 2100 MPa; The multi-anchor steel fiber has a nominal length of 6 to 13 mm, an equivalent diameter of 0.2 ± 0.02 mm, a breaking strength of ≥ 1200 MPa, an elastic modulus of 210 to 230 GPa, and a tensile strength of 550 to 2150 MPa; The temperature shrinkage induced organic fiber has a tensile strength of 500-1200 MPa, an elastic modulus of 7-35 GPa, a shrinkage rate of 0.5%-12%, and a response temperature of 30°C-100°C; The CaSO4 whisker has a nominal length of 100 to 300 μm, an equivalent diameter of 1 to 3 μm, and an apparent density of 2.3 to 2.6 g / cm 3 ; The CaCO3 whisker has a nominal length of 10 to 20 μm and an elastic modulus of 410 to 710 GPa.
4. The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to claim 3, characterized in that: The mass ratio of the P·II 52.5 silicate cement to the P·II 42.5 high iron phase sulphoaluminate cement containing the Q phase is (60-70):(30-40); The mass ratio of the fly ash, limestone, magnesite and calcium sulfate is (60-70):(15-20):(5-10):(5-10); The mass ratio of the red mud, limestone, bauxite and calcium sulfate is (40-45):(25-30):(20-25):(5-10); The Q phase-calcium sulphoaluminate clinker, The mass ratio of sulphoaluminate cement clinker is (50-60):(40-50); The mass of the dihydrate gypsum is 10-15% of the mass of the Q-rich P·II 42.5 high-iron phase sulphoaluminate cement clinker; The addition amount of the high-strength fine straight steel fiber is 20-30 kg / m 3 ; The addition amount of the multi-anchor steel fiber is 20-30 kg / m 3 ; The amount of the temperature shrinkage-induced organic fiber added is 1-2 kg / m 3 ; The amount of CaCO3 whiskers added is 5-8 kg / m 3 The amount of CaSO4 whiskers added is 5-8 kg / m 3 .
5. The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to claim 1, characterized in that: The viscosity-adjusting and reinforcing mineral admixture comprises a mixture of fly ash microbeads and silica fume; The amount of fly ash microbeads added is 75-100 kg / m 3 ; The amount of silica fume added is 75-100 kg / m 3 ; The fly ash microbeads have a 28d activity index of 107% and a water requirement ratio of 101%; The SiO2 mass content in the silica ash is ≥91%, and the specific surface area is ≥20100m 2 / kg, 28d activity index ≥101%.
6. The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to claim 1, characterized in that: The preparation method of the nano-silicon dioxide modified waterborne polyurethane emulsion is: Adding nano-silicon dioxide into an aqueous polyurethane emulsion, and uniformly dispersing the nano-silicon dioxide in the aqueous polyurethane emulsion by ultrasonic dispersion or high shear stirring, thereby obtaining a nano-silicon dioxide-modified aqueous polyurethane emulsion; The nano silicon dioxide has a particle size of 10 to 20 nm and a specific surface area of 200 to 400 m 2 / g, apparent density is 2.2~2.5g / cm 3 .
7. The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to claim 1, characterized in that: The highly efficient water-reducing, slump-retaining, foam-stabilizing and viscosity-adjusting admixture comprises a polycarboxylate water-reducing agent mother solution, an air-entraining agent, boric acid, a tetramethyldecynediol foam control agent, a polyhydroxycarboxylate retarder and water; Among them, the amount of polycarboxylate water-reducing agent mother liquor added is 6.1-6.2 kg / m 3 ; The amount of air entraining agent added is 0.003~0.005kg / m 3 ; The amount of boric acid added is 0.11~0.13kg / m 3 ; The amount of tetramethyldecynediol foam control agent added is 0.01-0.02 kg / m 3 ; The amount of polyhydroxycarboxylate retarders added is 0.11-0.13 kg / m 3 ; The amount of water added is 3.5-3.7 kg / m 3 .
8. The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to claim 1, characterized in that: The fine aggregate is river sand, and the apparent density of the fine aggregate is 2560-2650 kg / m 3 , the fineness modulus is 2.
8.
9. The multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to claim 1, characterized in that: The high-strength coarse aggregate is a basalt coarse aggregate with a continuous gradation of 5 to 16 mm. The basalt coarse aggregate has a strength of 169 MPa, a crushing value of 10%, a needle-like content of ≤5%, and an apparent density of 2900 to 3000 kg / m 3 .
10. A method for preparing the multi-scale toughening and shrinkage compensating C80 high crack resistance self-compacting concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: Low shrinkage and crack-resistant composite cement, viscosity-adjusting and reinforcing mineral admixtures, fine aggregate, high-strength coarse aggregate and multi-scale mixed fibers are mixed and stirred, and then water, high-efficiency water-reducing and collapse-preserving, foam-stabilizing and viscosity-adjusting admixtures, and nano-silicon dioxide-modified water-based polyurethane emulsion are added and stirred to obtain multi-scale toughening and shrinkage-compensating C80 high crack-resistant self-compacting concrete.
Citation Information
Patent Citations
Green high-strength high-temperature-resistant multi-scale fiber reinforced rubber concrete and preparation method thereof
CN116217182A
High-flow-state low-shrinkage high-toughness fiber concrete and preparation method thereof
CN117024068A
Fiber-free composite toughened and reinforced ultra-high performance concrete and preparation method thereof
CN118063163A